Aproveitamento da energia geotérmica superficial para aumentar a eficiência de condicionadores de ar e reduzir o pico de demanda - De Nardin, Carlos Roberto (2018)
This doctoral thesis is a contribution to reduce the electric load in thermal conditioning of residences in order to mitigate its influence on the duck curve. It is proposed the use of air conditioning units driven by photovoltaic generation to store thermal energy during their downtime. The thermal energy obtained can be stored during photovoltaic generation time and it can be used in a timely manner to attenuate the daily critical period of maximum demand from the electricity grid, just after the exit of the photovoltaic generation at dusk. This can be done by extracting surface geothermal energy from solar radiation and naturally stored in the soil. To prove its effectiveness, the necessary adaptations will be made in a conventional air conditioner and the incorporation of control and management instrumentation so that the air conditioner does not lose its original room conditioning function. The experiment was carried out simultaneously in two twinned rooms: one for the tests with geothermal energy and the other, a conventional room, both with similar physical areas, same geographical orientation and same thermal load. In the test room was installed an air conditioner with the modifications necessary to perform the extraction of surface geothermal energy and store it during the intervals of room conditioning and subsequent use. In the conventional room, called reference room was installed an air conditioner of the same type and model of the prototype in operation in the test room with its original features preserved for comparison of consumption of electric energy during the period of peak demand. This experiment proves that the thermal energy normally dissipated by the air conditioner in the external environment during the summer can be used to assist in heating of water for showers with the consequent reduction of the consumption of electric energy, collaborating to maximize the energy utilization.